2010
DOI: 10.1080/14786435.2010.495041
|View full text |Cite
|
Sign up to set email alerts
|

Nanotribology of Mo–Se–C films

Abstract: Transition metal dichalcogenides with a layered structure are well known for their self-lubricating properties, particularly in a vacuum or dry atmosphere. The macrotribological properties of these films have been studied extensively. However, the tribological behaviour of these films in the nanonewton load range has hardly been reported. Study of tribological properties with load in the nanonewton range is required for applications related to microelectromechanical systems or nanoelectromechanical systems. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The intensive and narrow peak at 2~ 44.5° was due to reflection from the steel substrate. The diffractograms of the MoS2 coatings were similar in many respects to those measured for transition metal-dichalcogenide-based coatings obtained through ion sputtering or PLD at room temperature [19,21,22,38]. The XRD patterns of these coatings showed an intense and broad peak near 2~ 13° and a pronounced peak at 2~ 33°, followed by a broad peak at 2~ 43°.…”
Section: The Structure and Composition Of Mos X Filmssupporting
confidence: 61%
See 1 more Smart Citation
“…The intensive and narrow peak at 2~ 44.5° was due to reflection from the steel substrate. The diffractograms of the MoS2 coatings were similar in many respects to those measured for transition metal-dichalcogenide-based coatings obtained through ion sputtering or PLD at room temperature [19,21,22,38]. The XRD patterns of these coatings showed an intense and broad peak near 2~ 13° and a pronounced peak at 2~ 33°, followed by a broad peak at 2~ 43°.…”
Section: The Structure and Composition Of Mos X Filmssupporting
confidence: 61%
“…The most common structural state of deposited coatings is "amorphous", which is generally assumed to form from nanoclusters with a lamellar structure typical of the 2H-MoS 2 phase [19][20][21][22]. Friction sliding is associated with the tribo-induced crystallization of such coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Although RMS surface roughness does not carry any information about slopes, sizes or frequencies of asperities, it is still an important parameter for predicting and understanding the properties of tribological systems [75]. Previous investigations with carbon films indicated that CoF increases with increase of roughness [76,77].…”
Section: Film Roughness Effect-lubricant Usementioning
confidence: 99%
“…Tomala et al 39 found that for W-S-C films, the atomic force microscopy (AFM) pull-off force increases with carbon content, and the friction force is highest for the film with the highest carbon content. Tomala et al 40 also noted that the pull-off force and wear decrease while the friction force and hardness increase with carbon content in Mo-Se-C films.…”
Section: Introductionmentioning
confidence: 95%